2001
DOI: 10.2105/ajph.91.2.225
|View full text |Cite
|
Sign up to set email alerts
|

Variation in youthful risks of progression from alcohol and tobacco to marijuana and to hard drugs across generations

Abstract: OBJECTIVES: Much research has documented that youthful substance use typically follows a sequence starting with use of alcohol or tobacco or both and potentially proceeding to marijuana and then hard drug use. This study explicitly examined the probabilities of progression through each stage and their covariates. METHODS: A secondary analysis of data from the National Household Survey on Drug Abuse (1979-1997) was conducted with particular sensitivity to the nature of substance use progression, sampling proced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(20 citation statements)
references
References 34 publications
(42 reference statements)
0
20
0
Order By: Relevance
“…SUAD was also described as the result of complex processes and multiple causes. For example, consistent with a “gateway” model (Golub & Johnson, 2001), a likely process could begin with alcohol and/or marijuana experimentation in order to fit in with peers; enjoyment of the feeling and camaraderie leading to continued use, later use for emotional coping, use of other substances; and progression to unintentional abuse and dependence or addiction. There were also small differences between communities in reported SUAD risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…SUAD was also described as the result of complex processes and multiple causes. For example, consistent with a “gateway” model (Golub & Johnson, 2001), a likely process could begin with alcohol and/or marijuana experimentation in order to fit in with peers; enjoyment of the feeling and camaraderie leading to continued use, later use for emotional coping, use of other substances; and progression to unintentional abuse and dependence or addiction. There were also small differences between communities in reported SUAD risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…In a review of the literature, only one study indicated that early age of alcohol use was associated with later IDU (Corsi, Winch, Kwaitkowski, & Booth, 2007) and one study indicated that the age of first alcohol use was significantly younger for injection drug users compared with non-injection drug users (Sherman et al, 2005). In addition, research has suggested that early onset of alcohol-related disorders may predict the use of heavier drugs (Golub & Johnson, 2001; Merrill, Kleber, Shwartz, Liu, & Lewis, 1999) as well as alcohol abuse/dependence or other drug dependence (Chen, Storr, & Anthony, 2009; Dawson, Goldstein, Chou, Ruan, & Grant, 2008; Grant, 1998; Grant & Dawson, 1997; Grant, Stinson, & Harford, 2001; King & Chassin, 2007) later in life.…”
Section: Adolescent Alcohol Initiation and Illicit Drug Usementioning
confidence: 99%
“…Moreover, cannabis is related to a myriad of negative outcomes, including psychological symptoms and disorders (Patton et al, 2002; Zvolensky et al, 2006), and tobacco smokers are more likely to use cannabis (Ford et al, 2002). Coupled with tobacco and alcohol use, cannabis use has adverse effects on fetal growth and development (Cornelius et al, 2002; Richardson et al, 1995), increases risk for harder drugs (Golub and Johnson, 2001), and negatively impacts educational achievements (Centers for Disease, 1991; Martin et al, 1992). Interventions for co-occuring substance use have demonstrated favorable effects (Chariot et al, 2014; Gmel et al, 2013; Laporte et al, 2014).…”
Section: Introductionmentioning
confidence: 99%